Club convergence of labour productivity in agriculture: Evidence from EU countries - Arkadiusz Kijek; Tomasz Kijek; Anna Nowak (Agricultural Economics (AGRICECON), 2020)
This paper studies club convergence in relation to labour productivity in the agriculture industry of 28 European Union countries for the period 2005 to 2018. The countries were divided into three groups which were homogeneous in terms of level of development in the agricultural sector. The presence of convergence in the groups of countries was verified by using a panel-data model of conditional β-convergence. Then, convergence processes were investigated within clubs of countries. Convergence processes took place in the groups of countries with low and medium levels of labour productivity. In the club of countries where labour productivity was high, opposite processes (i.e. divergence) were observed.